Strategies for Teaching Islamic Inheritance Law at the Salafiyah Wonoyoso Kebumen Madrasah - Nurtofik; Marwan Setiawan (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2026)
The purpose of this study is to examine how learning approaches, mediums, and methodologies are used similarly and differently for in learning Islamic inheritance law at Madrasah Aliah Salafiyah Wonoyoso Kebumen. Descriptive qualitative research was used. Observation, documentation, and data was gathered via interviews. The study's findings indicate that the other objectives from learning Islamic inheritance law at Madrasah Aliah Salafiyah Wonoyoso Kebumen are the same, namely learning how to divide inheritance. However, there are differences in the delivery method. MA Salafiyah's approach remains teacher-focused, while MA Salafiyah Wonoyoso's approach focuses more on students. MA Salafiyah Wonoyoso's approach Increase your usage of lectures and Q&A techniques, but MA Salafiyah Wonoyoso's approach also uses various methods, such as talks, queries, and responses, assignments. If seen, the use of media is the same, namely using a whiteboard and markers. However, MA Salafiyah also uses laptops and LCD projectors.